CO2 capture on natural zeolite clinoptilolite: Effect of temperature and role of the adsorption sites. (1st December 2020) - Davarpanah, E.; Armandi, M.; Hernández, S.; Fino, D.; Arletti, R.; Bensaid, S.; Piumetti, M.
Abstract: In this study, the adsorption capacity of the low-cost zeolite clinoptilolite was investigated for capturing carbon dioxide (CO2 ) emitted from industrial processes at moderate temperature. The CO2 adsorption capacity of clinoptilolite (a commercial natural zeolite) and ion-exchanged (with Na + and Ca 2+ ) clinoptilolite were tested under both dynamic (using a fixed-bed reactor operating with 10% vol. CO2 in N2 ) and equilibrium conditions (measuring single component adsorption isotherms). The dynamic CO2 adsorption capacity of bare clinoptilolite and ion-exchanged clinoptilolite were evaluated in the temperature range from 293 K to 338 K and the obtained breakthrough curves were compared with those of the commercial zeolite 13X (Z13X). Although the adsorption capacity of Z13X exceeded those of bare clinoptilolite and ion-exchanged clinoptilolite at 293 K, the clinoptilolite exhibited the highest CO2 uptake at a moderate temperature of 338 K (i.e. 25 % higher than Z13X). This feature appears in agreement with the lower isosteric heat of CO2 adsorption on clinoptilolite compared to the other samples. The surface species affecting the q iso and adsorption capacity were investigated through the FTIR spectroscopy using CO2 as probe molecule. As a whole, it has been observed that CO2 forms linear adducts onto K + and Mg 2+ cations of the bare clinoptilolite, and carbonate-like species onto its basic sites. With the Na-exchanged clinoptilolite, Na + ions led to a decrease in surface basicity and to the formation of both single (Na + ···OCO) and dual (Na + ···OCO⋯Na + ) cationic sites available for the formation of linear adducts. As a result of the remarkable adsorption capacity of clinoptilolite at 338 K, this material appears to be a promising adsorbent for the direct CO2 removal from different flue gases sources operating at such temperatures. Graphical abstract: Image 1 Highlights: Clinoptilolite can be a sustainable CO2 capture material at moderate temperature. At moderate T (338 K), the CO2 adsorption uptake scale is Clino > Z13X ≈ Na-Clino. The lower q iso of bare Clino favours CO2 adsorption at high temperature. CO2 forms linear adducts onto K + and Mg 2+ ions and carbonates onto basic sites. With Na-Clino, CO2 linear adducts form onto Na + ions and lead to higher q iso .